A comparison of the description of nature between Ibn zaydun and Ahmad Shawqi - Sheng, Du; Ismail, Muhd Zulkifli; Syed Abdullah, Syed Nurulakla; Wan Sulong, Wan Muhammad (Al-Kindi Center for Research and Development, 2024)
This study examines the description of nature in the poems of Ibn Zaydun (سلوتم وبقينا) and Ahmad Shawqi (تلك الطبيعة). Ahmad Shawqi was influenced by the style and content of Ibn Zaydun's poetry, and he composed his poems in response to Ibn Zaydun’s works. The researcher compares the two poems in order to identify their points of convergence and divergence. The study then analyzes the artistic imagery through which the two poets depicted nature and its elements, as well as the key techniques they employed to render these images, such as simile and metaphor. The researcher concludes by highlighting the similarities and differences in the poetic characteristics of both poets, revealing how Ahmad Shawqi innovated new forms of art and created new styles in his depiction of nature.